Molecular Characterization of Avian Pathogenic Escherichia coli Isolates using Virulence Associated Genes - Limbachiya, Bhargav B.; Mathakiya, Rafiyuddin A.; Sinha, Esha; Mathakiya, Anik M. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Among various diseases, colibacillosis is one of the most important diseases, which causes heavy economic losses in broilers as well as in layers. It is caused by pathotype avian pathogenic E. coli (APEC). The present research work was carried out to detect and characterize the 60 Escherichia coli isolates. All the preserved isolates were obtained from various poultry farms located in and around Anand, Gujarat. All the isolates were revived and confirmed by polymerase chain reaction using phoA gene followed by characterization of the isolates based on seven virulence associated genes, viz., astA, iss, vat, papC, iucD, irp2 and tsh. Out of the 60 E. coli isolates analysed, the overall highest positive percentage was for gene iss (93.34%), followed by iucD (60.00%), irp2 (46.67%), astA (40%), tsh (33.33%), vat (26.67%) and papC (15.00%), respectively.